PENGARUH iRELATIONSHIP iQUALITY iTERHADAP iLOYALITAS iDENGAN iCUSTOMER iRETENTION iSEBAGAI iVARIABEL iINTERVENING iPADA iNASABAH iTABUNGAN iPT. iBANK iBTN iCABANG iSYARIAH iMALANG - Aldila Nur Rafika Putri; Yayuk Sri Rahayu (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2023)
This study aims to determine and analyze the effect of relationship quality on loyalty with customer retention as an intervening variable on savings customers of PT. Bank BTN Malang Syariah Branch. The population in this study were customers of PT. Bank BTN Malang Syariah Branch. The researcher took a sample of 100 respondents using a purposive sampling technique, with the criteria of the respondents being savings customers who actively make transactions at PT.Bank BTN Malang Sharia Branch, savings customers who have used bank services for at least 1 year, and savings customers who make repeated transactions. The research hypothesis was tested using the Partial Least Square (PLS) based Structural Equation Model (SEM) approach. The results obtained from this study indicate that relationship quality has a significant effect on customer retention, customer retention has a significant effect on loyalty, and relationship quality has a significant effect on loyalty.